Enzyme-mediated transglycosylation of rutinose (6-O-α-L-rhamnosyl-D-glucose) to phenolic compounds by a diglycosidase from Acremonium sp. DSM 24697 - Mazzaferro, Laura (2019)
The structure of the carbohydrate moiety of a natural phenolic glycoside can have a significant effect on the molecular interactions and physicochemical and pharmacokinetic properties of the entire compound, which may include anti-inflammatory and anticancer activities. The enzyme 6-O-α-rhamnosyl-β-glucosidase (EC 3.2.1.168) has the capacity to transfer the rutinosyl moiety (6-O-α-L-rhamnopyranosylβ-D-glucopyranose) from 7-O-rutinosylated flavonoids to hydroxylated organic compounds. This transglycosylation reaction was optimized using hydroquinone (HQ) and hesperidin as rutinose acceptor and donor, respectively. Since HQ undergoes oxidation in a neutral to alkaline aqueous environment, the transglycosylation process was carried out at pH values 6.0. The structure of 4-hydroxyphenyl-β-rutinoside was confirmed by NMR, that is, a single glycosylated product with a free hydroxyl group was formed. The highest yield of 4-hydroxyphenyl-β-rutinoside (38%, regarding hesperidin) was achieved in a 2-h process at pH 5.0 and 30 ◦C, with 36 mM OH-acceptor and 5% (v/v) cosolvent. Under the same conditions, the enzyme synthesized glycoconjugates of various phenolic compounds (phloroglucinol, resorcinol, pyrogallol, catechol), with yields between 12% and 28% and an apparent direct linear relationship between the yield and the pKa value of the aglycon. This work is a contribution to the development of convenient and sustainable processes for the glycosylation of small phenolic compounds.